(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Megersa M, Dida G, Gadissa F, Sebsibe A, Germame A, Alemayehu G, Kebede B, Bekele D, Belachew S. 2022. Food, medicinal plants, and homemade beverages, used as a response to the pandemic in Ethiopia. Biodiversitas 23: 2146-2155. SARS-CoV-2, which is responsible for an infectious disease called COVID-19, significantly impacted the global community, including Ethiopia. Meanwhile, people responded to the disease in various ways using available household materials. These include food, medicinal plants, and household beverages used for preventing and curing symptoms of COVID-19. Thus, the present study was initiated to assess these foods, medicinal plants, and beverages used in Ethiopia during the COVID-19 pandemic. This study used a web-based survey and phone call to collect data related to food, medicinal plants, and beverages used during COVID-19 by emphasizing medicinal plants. The questionnaire was created through Google Form and circulated through social media such as Facebook, Telegram, and Whatsapp. A total of 680 respondents took part in the survey. Relative citation frequencies (RFC) were calculated to assess popular medicinal plants used to prevent or mitigate the disease. A total of 53 medicinal plants used to prevent and cure COVID-19 distributed to 24 families were recorded. Leaves (30%) were the most frequently utilized plant part. The respondents indicated that they were using medicinal plants for COVID-19 prevention at least once a day, accounting for (41.3%). Most of them recommended using medicinal plants to prevent the disease. Relative frequency of citation (RFC) indicated that Zingiber officinale Roscoe was the most popular medicinal plant used during the pandemic. Apart from medicinal plants, foods and beverages were also frequently used during the pandemic. The majority of respondents (49.6%) mentioned that local communities were their source of information. Respondents also indicated the use of the medicinal plant has increased during the first three months of the COVID-19 pandemic claiming that they have the potential to prevent and cure COVID-19. However, this should not be considered a panacea since the effectiveness of these medicinal plants, foods, and beverages has not been confirmed.